2014
DOI: 10.1088/0004-637x/790/2/153
|View full text |Cite
|
Sign up to set email alerts
|

Particle Energization During Solar Maximum: Diffusive Shock Acceleration at Multiple Shocks

Abstract: We present a model for the acceleration of particles at multiple shocks using an approach related to box models. A distribution of particles is diffusively accelerated inside the box while simultaneously experiencing decompression through adiabatic expansion and losses from the convection and diffusion of particles out of the box by either the method used in Melrose & Pope and Pope & Melrose or by the approach introduced in Zank et al. where we solve the transport equation by a method analogous to operator spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…3. In Matthaeus et al (2003) it was suggested to approximate fourth-order correlations involving particle velocity vector components and magnetic field vector components by a product of two second-order correlations (see Equation (21) of the current paper). As shown in Figures 1-5, this approximation is not valid.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3. In Matthaeus et al (2003) it was suggested to approximate fourth-order correlations involving particle velocity vector components and magnetic field vector components by a product of two second-order correlations (see Equation (21) of the current paper). As shown in Figures 1-5, this approximation is not valid.…”
Section: Discussionmentioning
confidence: 99%
“…By combining Equations (13) and 14, we can compute the coefficient k xx GC . In linear and nonlinear analytical treatments of perpendicular diffusion, one usually starts with the following equation of motion (see, e.g., Matthaeus et al 2003):…”
Section: Diffusion Coefficients Via Velocity Correlationsmentioning
confidence: 99%
See 3 more Smart Citations